Physico-mechanical properties of porcelain by substitution of quartz with POFA Treated with 2M Hcl acid - Sani Garba., Durumin Iya; Noh, Mohamad Zaky; Ab Razak, Siti Noraiza; Alwi Kutty, Nur Azureen (Science Publishing Corporation, 2018)
Palm oil fuel ash (POFA) is a by-product from thermal power plant where palm kernel, shell and fibre used as fuel to generate electricity and disposed with no economic value. POFA is used as quartz replacement in the production of porcelain. POFA was dried in an oven for 24 hours at 110 °C, ground at a speed of 250 rev/sec for 12 hrs. Some of the POFA amount was treated with 2 Molar of HCl acid and some was kept untreated. Both treated and untreated were substituted with quartz at 15 wt% and mixed with porcelain composition and dry pressed into pellets at a mould pressure of 91 MPa and sintered at 1150 °C, 1200 °C and 1250 °C for 2 hrs soaking time respectively. XRF revealed that, POFA has similar chemical composition with quartz. The highest compressive strength, bulk density and Vickers microhardness being achieved at sintering temperature of 1150 °C using treated sample with the values 169 MPa, 2.432 g/cm3 and 774 HV respectively. HCl treated POFA is a good candidate for quartz replacement and 1150 °C was the best sintering temperature.